2020
DOI: 10.1002/ccd.29259
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement with Evolut R versus Sapien 3 in Japanese patients with a small aortic annulus: The OCEAN‐TAVI registry

Abstract: Objectives To compare safety, efficacy, and hemodynamics of transfemoral transcatheter aortic valve replacement (TAVR) using self‐expanding and balloon‐expandable transcatheter heart valves (THVs) in patients with a small aortic annulus. Background Few studies have directly compared TAVR outcomes using third‐generation THVs, focusing on patients with small aortic annuli. Methods In a multicenter TAVR registry, we analyzed data from 576 patients with a small annulus and who underwent transfemoral TAVR using thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…Compared with the balloon-expandable SAPIEN 3 valve, 7/10 https://e-kcj.org https://doi.org/10.4070/kcj.2020.0409 the self-expanding Evolut R valve showed superior hemodynamic outcomes (iEOA, 1.08 vs. 1.2 cm 2 /m 2 , p<0.001; mean aortic valve pressure gradient, 12.0 vs. 9.0 mmHg, p<0.001). 15) However, no significant difference was noted in the incidence of moderate and severe PPM which was different from our study. This may be due to the difference in study population with smaller BSA compared to the study of ours and Mauri et al 5) Clinically significant PPM was identified as a predictor of adverse clinical outcomes after TAVR.…”
Section: Tavr In Patients With Small Aortic Annuluscontrasting
confidence: 99%
See 1 more Smart Citation
“…Compared with the balloon-expandable SAPIEN 3 valve, 7/10 https://e-kcj.org https://doi.org/10.4070/kcj.2020.0409 the self-expanding Evolut R valve showed superior hemodynamic outcomes (iEOA, 1.08 vs. 1.2 cm 2 /m 2 , p<0.001; mean aortic valve pressure gradient, 12.0 vs. 9.0 mmHg, p<0.001). 15) However, no significant difference was noted in the incidence of moderate and severe PPM which was different from our study. This may be due to the difference in study population with smaller BSA compared to the study of ours and Mauri et al 5) Clinically significant PPM was identified as a predictor of adverse clinical outcomes after TAVR.…”
Section: Tavr In Patients With Small Aortic Annuluscontrasting
confidence: 99%
“… 5) 6) The main factor to achieve better hemodynamic benefits and larger EOA may be driven by supra-annular location in the self-expanding valve compared with intra-annular location in the balloon-expandable valve. Recently, Hase et al 15) focused on Japanese patients with small aortic annulus defined as mean annulus diameter ≤23 mm on computed tomography. Compared with the balloon-expandable SAPIEN 3 valve, the self-expanding Evolut R valve showed superior hemodynamic outcomes (iEOA, 1.08 vs. 1.2 cm 2 /m 2 , p<0.001; mean aortic valve pressure gradient, 12.0 vs. 9.0 mmHg, p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…obesity and impaired left ventricular function), a small native aortic annulus was associated with increased rates of PPM [7]. Recent analyses favored supra-annular transcatheter heart valves (THV) for the treatment of patients with severe aortic stenosis and a small aortic annulus (SAA) [8][9][10]. However, several additional THV designs have become commercially available in the meantime and optimal valve selection for patients with SAA remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Schofer et al reported data from 1,309 patients undergoing TAVI with intraannular BEV, supra-annular SEV, intra-annular SEV, cusp-fixated SEV, mechanically expandable infra-annular valve, and nonmetallic valve: the lowest rate of severe PPM was present with supra-annular SEV (4%), whereas the highest rate of severe PPM was detected in patients with self-expandable cusp-fixated (25%) and intra-annular BEV (24%) (38). In a recent further analysis of propensity score-matched patients from the OCEAN-TAVI registry treated with third-generation THV, Evolut R seemed to be superior to Sapien 3 in hemodynamic performance in terms of mean pressure gradient and iEOA (78).…”
Section: Self-expandable Valvesmentioning
confidence: 94%